Analisis Kepuasan Tamu Terhadap Pelayanan Petugas Penerima Tamu (Guest Service Agent) Di Pangeran’s Beach Hotel Padang (Studi Kasus Tamu Pria Dan Wanita) - Rihendra Rihendra; Djoko Sudibyo; Adhi Trirachmadi Mumin (Jurnal Public Administration, Business and Rural Development Planning, 2019)
A good hotel is able to benefit by providing satisfaction for its guests. In the hotel we have to try to motivate the employees to understand the importance of giving satisfaction to the guests. It is also necessary to try and see things from the viewpoint of the guests. What are favored by guests? What will please the guests? And what can make him happy? Is it possible to provide the service desired by the guest in order to achieve these objectives? How can we improve the service? How can we help something simpler the better. In connection with these questions, the hotel staff especially the conciergePrince'sBeach Hotel Padang must realize that guest satisfaction is more important than the satisfaction of the leadership, making employees guest who are in the business world this hotel.To be able to meet the desires and needs of the service, then there are some things that must be considered by the concierge Prince's Beach Hotel Padang that the services provided to guests and attitude (performance) at the time of serving guests arrive. This research uses descriptive quantitative approachto sampling techniques stay guests who by chance meet to be given a questionnaire. Analysis of data using a Likert scale to determine how far the service and attitude reception of providing services.